Peningkatan Pengetahuan Lansia tentang Hipertensi Emergensi melalui Pendidikan Kesehatan - Isnaini Rahmawati; Dewi Suryandari; Noerma Shovie Rizqiea (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Hypertension is a disease that not many people know before examining their blood pressure, so it is called with silent disease. Increased self-knowledge of this disease becomes the basis for individuals to make the decisions for the treatment. With good knowledge, we hope that the effects and complications of hypertension can be prevented. For this reason, health education is needed regarding hypertensive emergencies in elderly, because the elderly include in one of the groups at risk for hypertension, this is due to a decrease in physiology from increasing age. The purpose is to increase the elderly's knowledge about hypertensive emergencies, so as to prevent the occurrence of these events. Methods: Health education through counseling during posyandu activities was used in this activity, the knowledge was measure using questionnaire. Results: After this activity, the elderly understood about hypertensive emergencies and also knew what steps should be taken if such an event occurs. Conclusion: The increasing about knowledge in definition was 82,1%, the sign and symptom was 52%, and the treatment was 45%.